Creating job satisfaction in a strict organization - Setiawan, Roy; Eliyana, Anis; Suryani, Tatik; Christopher, Jonathan (Opción, 2020)
One solution that can increase employee satisfaction is perceived organizational support, which will create work engagement and reduce work holism. This research uses quantitative research methods, with a sample of 165 respondents taken by random sampling techniques at chemical companies in Indonesia. The results showed that perceived organizational support did not affect job satisfaction and perceived organizational support had no effect on work engagement. Besides, perceived organizational support had no effect on work holism and work engagement had an effect on job satisfaction. Moreover, perceived organizational support does not affect job satisfaction through work holism as a mediating variable.